Etika Komunikasi Generasi Z Dan Generasi Milenial Dalam Media Sosial Tiktok - Aulia, Muhammad Mirza Rizky; Christin, Maylanny (eProceedings of Management, 2024)
Problems often faced in the context of social media in Indonesia include the spread of fake news (hoaxes), hate speech,cyberbullying, and privacy violations. TikTok's popularity among Generation Z and Millennials makes it an idealplatform to study how these generations understand and apply communication ethics in the digital era. The researchmethod used is a descriptive qualitative research method. Overall, This study reveals the differences in views betweenMillennials and Generation Z regarding communication ethics on TikTok and its impact on social interactions.Millennials emphasize honesty, accuracy, and social responsibility, while Generation Z prioritizes authenticity andemotional connectedness, sometimes at the expense of accuracy. Both generations show a high awareness of theimportance of respecting individual rights and dignity. The impact of ethical violations includes a decline in reputationand quality of interactions. Awareness-raising efforts through education, creative campaigns, and effective contentmoderation are considered important by both. TikTok has a crucial role to play in supporting and enforcing ethicalcommunication standards on the platform. Keywords-communication ethics, generation z, millennial generation, TikTok